Hepatocyte growth factor is elevated in amniotic fluid from obese women and regulates placental glucose and fatty acid metabolism. Issue 4 (April 2015) - Visiedo, F.; Bugatto, F.; Carrasco-Fernández, C.; Sáez-Benito, A.; Mateos, R.M.; Cózar-Castellano, I.; Bartha, J.L.; Perdomo, G.
Abstract Introduction To evaluate the impact of the pro-inflammatory cytokine hepatocyte growth factor (HGF) on the regulation of glucose and lipid placental metabolism. Methods HGF levels were quantified in amniotic fluid and placenta from control and obese women. 2-deoxy-glucose (2-DOG) uptake, glycolysis, fatty acid oxidation (FAO), fatty acid esterification, de novo fatty acid synthesis, triglyceride levels and carnitine palmitoyltransferase activities (CPT) were measured in placental explants upon addition of pathophysiological HGF levels. Results In obese women, total- and -activated-HGF levels in amniotic fluid were elevated ∼24%, and placental HGF levels were ∼3-fold higher than in control women. At a similar dose to that present in amniotic fluid of obese women, HGF (30 ng/mL) increased Glut-1 levels and 2-DOG uptake by ∼25–30% in placental explants. HGF-mediated effect on 2-DOG uptake was dependent on the activation of phosphatidylinositol 3-kinase signaling pathway. In addition, HGF decreased ∼20% FAO, whereas esterification and de novo fatty acid synthesis increased ∼15% and ∼25% respectively, leading to 2-fold triglyceride accumulation in placental explants. In parallel, HGF reduced CPT-I activity ∼70%. Discussion HGF is a cytokine elevated in amniotic fluid and placental tissue of obese women, which through its ability to stimulate 2-DOG uptake and metabolism impairs FAO and enhances esterification and de novo fatty acid synthesis, leading to accumulation of placental triglycerides.